Assessing the current state of juvenile probation practice: A statutory analysis. Issue 5 (3rd July 2016) - Hsieh, Ming-Li; Woo, Youngki; Hafoka, Moana; van Wormer, Jacqueline; Stohr, Mary K.; Hemmens, Craig
ABSTRACT: The 2002 Desktop Guide to Good Juvenile Probation Practice indicated that a state's juvenile justice system should reflect a "balanced and restorative justice" (BARJ) model. Over a decade has passed since this publication, yet little is known about whether juvenile probation followed the BARJ. This study employed a statutory analysis to examine the differences between the legally prescribed roles of juvenile probation officers and the BARJ model across 50 states and the District of Columbia. Results indicated that even with significant reforms and statutory changes overtime, juvenile probation practices still fall short of meeting the basic tenets of restorative justice.